Evaluation Of The Effect Of RukshaBasti Along With Suryanamasakar And Nadishodhan Pranayama In The Management Of Sthaulya (Obesity) - Gupta, Ved Prakash; Marwaha, Nitin; CharuBansal (International Research Journal of Ayurveda & Yoga, 2020)
The aim of present study was evaluation of the effect of rukshabasti along with suryanamasakar and nadishodhan pranayama in the management of sthaulya (obesity).Sthaulya (Obesity) is one among the major disease of modern era with continuous changing life style, environment and diet habits. Atisthaulya (obesity) is considered as one of the Astanindita purush as described by Acharya Charak. Obesity has reached epidemic proportions in India in the 21st century, with morbid obesity affecting 5% of the country’s population. Though, many theory and medicament put toward us for the management of the obesity but till now perfect remedy for this problem is not found in modern science. In Ayurvedic classics various treatment modality given for the management of obesity like Udvartan, Basti, Vyayam, Langhana etc. Keeping of this view this study were selected Suryanamaskar, Nadishodhana Pranayama and Ruksha Basti both are having great potential to control and cure the obesity. In this study 60 patient were selected and divided into 30 for each group according to inclusion criteria. In Group A Patients were advised Ruksha Basti, Suryanamskar and Nadishodhan Pranayama and in Group B Patients were advised only Yoga procedure Suryanamskar and Nadishodhan Pranayama. After the completion of treatment statistical analysis revealed that according mean difference and percentage relief all subjective and objective parameter Group “A” Showed better result than Group “B”.